Kinerja Kader Pada Peningkatan Minat Kunjungan Ke Posyandu di Desa Mekarlaksana - Hani Suryani; Alda Ramadhika (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
In the world of work and organizations, performance is very important in an organization because it determines the success in achieving the goals and vision of an organization. This study aims to determine the extent to which the role of cadre performance on increasing interest in visiting posyandu. The resulting output is community satisfaction with the services provided. The research method used in this research is descriptive qualitative to explore thoroughly and in depth about the performance of cadres in the Mekarlaksana Village posyandu. Data were collected by means of interviews, observation and documentation to harmonize the facts in the field with existing data. And analyzed by means of data collection, data reduction, data presentation and conclusion drawing. The results showed that the performance of cadres had an impact on community interest in visiting. Most people feel comfortable with the services provided so that visits to the posyandu increase and stabilize. This finding indicates that performance affects people's desire to visit. Thus, this study contributes to the management of social organizations and can be used as a reference for further research.